A novel approach towards deriving vocabulary quotient. (10th May 2018) - Rajput, Nikhil Kumar; Ahuja, Bhavya; Riyal, Manoj Kumar
Abstract: A Shannon's entropy-based measure for assessing a person's vocabulary strength has been proposed, which has been termed vocabulary quotient. The measure proposed has been made independent of the text size by normalization and determines the degree of uniqueness in the document. It takes into consideration the number of different words used and the frequency of their usage. The vocabulary quotient has been calculated for two cases: one over the original and the other on the text after the removal of function words. The value obtained in the second case serves as a more reasonable quantification, as content words give a more realistic view of a person's vocabulary. The measure, hence, computed can also be used to determine vocabulary growth of a person over time.